COMPARATIVE STUDY OF IMPLICATION FOR IMPLEMENTING COPYRIGHT LAW AND BOOK LAW IN THE LIBRARY COLLECTION SERVICE - Mohamad Pandu Ristiyono; Ratna Nurhayati (Faculty of Law, Universitas Sebelas Maret, 2019)
This article examines the implication of Copyright Law and Book Law implementation of the service in the library. The research method used is normative juridical legal. Thecorrelation between the Book Law, Law on Handover of Print and Recorded Worksand the Library Law, both are lex specialist derogate generalist of the CopyrightLaw or not, according to the author is the adoption or depiction of the fair use andfair dealing doctrine as which is the social function of copyright. The CopyrightLaw provides protection for Author and Copyright Holder with exclusive rights tobe exploited. Related to the Law on Handover of Print and Record Works whichgives the obligation of the Author or Copyright Holder to deposit their work for thepurpose of preservation and other social purposes to the library which is regulatedin the Library Law